Decentering Nations: The Role of National Institutes for Culture in the Promotion and Circulation of European Cinema (Cinéma & Cie. Film and Media Studies Journal, 2024)
When considering the circulation of European films across Europe within a post-national framework, an investigation on the role of national institutes for culture could offer a particular take on the “Europeanisation” (Carpentier 2021) process through cinema-related initiatives. If they were conceived to promote national heritage and values, they have found themselves in the ambivalent position of pursuing their main goal within a changing institutional and cultural context that requires more integrated approaches, since the beginning of the 1990s, namely after the end of the Cold War. Notably, since the creation of the European National Institutes for Culture network (hereafter EUNIC) in 2006, they have been asked to cooperate and to valorise the heterogeneity and multiplicity of European subjectivities and communities, according to the motto “unity in diversity” (Liz 2016; Bondebjerg, Novrup Redvall, and Higson 2014). In particular, this research concentrates on the circulation, among European and Italian institutes for culture, of films that deal with European issues, and has reflected on how they affect the construction of a transnational European identity by addressing sensitive topics.
Keywords: Post-nationalism; Transnational Identity(ies); Policy Making; European Institutes of Culture; Film Diplomacy